CDK4/6 inhibition antagonizes the cytotoxic response to anthracycline therapy - McClendon, A. Kathleen (Landes Bioscience, 2012)
Triple-negative breast cancer (TNBC) is an aggressive disease that lacks established markers to direct therapeutic intervention. Thus, these tumors are routinely treated with cytotoxic chemotherapies (e.g., anthracyclines), which can cause severe side effects that impact quality of life. Recent studies indicate that the retinoblastoma tumor suppressor (RB) pathway is an important determinant in TNBC disease progression and therapeutic outcome. Furthermore, new therapeutic agents have been developed that specifically target the RB pathway, potentially positioning RB as a novel molecular marker for directing treatment. The current study evaluates the efficacy of pharmacological CDK4/6 inhibition in combination with the widely used genotoxic agent doxorubicin in the treatment of TNBC. Results demonstrate that in RB-proficient TNBC models, pharmacological CDK4/6 inhibition yields a cooperative cytostatic effect with doxorubicin but ultimately protects RB-proficient cells from doxorubicin-mediated cytotoxicity. In contrast, CDK4/6 inhibition does not alter the therapeutic response of RB-deficient TNBC cells to doxorubicin-mediated cytotoxicity, indicating that the effects of doxorubicin are indeed dependent on RB-mediated cell cycle control. Finally, the ability of CDK4/6 inhibition to protect TNBC cells from doxorubicin-mediated cytotoxicity resulted in recurrent populations of cells specifically in RB-proficient cell models, indicating that CDK4/6 inhibition can preserve cell viability in the presence of genotoxic agents. Combined, these studies suggest that while targeting the RB pathway represents a novel means of treatment in aggressive diseases such as TNBC, there should be a certain degree of caution when considering combination regimens of CDK4/6 inhibitors with genotoxic compounds that rely heavily on cell proliferation for their cytotoxic effects.